SURFACE PARAMETERISATION OF THE UTERO/PLACENTAL INTERFACE USING 3D POWER DOPPLER ULTRASOUND - Stevenson, G; Collins, S; Impey, L; Noble, J; IEEE (2011)
Studying the surface of an internal organ such as the placenta using three-dimensional ultrasound (3D US) is difficult. Image data from the surrounding tissue makes accurate identification of the interface technically challenging. The placental/maternal interface (basal plate) is thought to be the location of significant vascular pathology causing major maternal and fetal morbidity. We propose a new method for identifying this interface which combined with parameterisation (flattening) offers a novel way to study the vasculature of the developing placenta. © 2011 IEEE.